Curcumin's Protective Role in Heatstroke‐Induced Acute Liver Injury: Targeting Pyroptosis and Enhancing SIRT1 Expression - Yizhan Wu; Fei Guo; Yan Ma; Weihao Chai; Jiajia Li; Wenhui Shi; Jiangwei Liu (Global Challenges)
Abstract Heatstroke (HS) is a severe systemic condition that significantly impacts organ function, with the liver being particularly vulnerable. Sirtuin 1 (SIRT1), a crucial deacetylase, is implicated in various diseases' pathophysiology. Curcumin, a natural polyphenol, has been shown to modulate SIRT1 activity, offering therapeutic benefits. This study explores the impact of HS on hepatic SIRT1 expression and the protective mechanisms of curcumin against HS‐induced hepatic injury. Male C57BL/6 mice are divided into control and curcumin pretreatment groups, subjected to HS induction, and assessed for liver injury biomarkers, oxidative stress, and inflammatory cytokines. Results indicate that HS downregulates SIRT1, leading to liver damage and systemic inflammation. Curcumin pretreatment dose‐responsively attenuates these effects, with the highest dose providing optimal protection, potentially through SIRT1 restoration. The findings suggest that curcumin's hepatoprotective role in HS may be mediated by upregulating SIRT1, highlighting its therapeutic potential in heatstroke‐related liver damage.